Ultra Short-Term Heart Rate Recovery After Maximal Exercise in Two Different Body Positions in Elite Male Judokas Compared to Students of the Sport Faculty - Sandra Vujkov; Cristina Casals; Željko Krneta; Patrik Drid (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2016)
Heart Rate Recovery response to exercise has been recognized as a marker of physical fitness. Therefore, the aim of this study was to determine the effects of two different recovery protocols (supine and standing position) on heart rate during the first minute of recovery with a group of elite male judokas and group of students, after maximal progressive treadmill test. Twenty-four male participants took part in this study, twelve (n=12) judokas (Serbian national team) and twelve (n=12) stu¬dents as a control group. They were exposed to maximal progressive exercise treadmill test in order to record HR (bpm) during the test and during the first minute of recovery. One-way analysis of variance with repeated measures is used to test the differences bet¬ween subjects' responses over time. Statistical significance was assessed using ANCOVA and Student's t-test for dependent samples. HRmax was similar in both trials for investigated groups. The results of Student's t test showed significant differences between applied protocols in all HR levels for both groups. In addition, the within subjects effects for supine protocol showed significant differences between groups (F=14.172, P=0.0001), where the group of judokas revealed lower HR than students for 10s and 20s of recovery period (F=18.801 and F=19.668, p<0.01, respectively). Obtained data could suggest better adaptation to exercise for trained judokas in exerting better potentials with faster recovery HR immediately after the exercise in supine position, consequently revealing better adaptation to training load.